Evaluating the Performance of Anaerobic Digestion with Upstream Thermal Hydrolysis—What Role Does the Activated Sludge Process Play? - Johannes Rühl; Markus Engelhart (Fermentation)
The performance of anaerobic digestion of mixed sludge (MS) with upstream thermal hydrolysis of waste activated sludge (WAS) was evaluated and compared to conventional anaerobic digestion. In contrast to previous studies, this work focuses on the evaluation of the impact of the activated sludge process, which was assessed using a temperature-normalized solids retention time (SRTASP,T). For this purpose, data from a full-scale wastewater treatment plant related to SRTASP,T, primary sludge (PS) and WAS production were combined with experimental data from laboratory-scale anaerobic digestion of PS, WAS, thermally hydrolyzed WAS, and MS. The parameter SRTASP,T was used as a key link between the full-scale and experimental data. For WAS, SRTASP,T essentially influenced the efficacy of thermal hydrolysis on the performance of anaerobic digestion. The increase in methane yield was higher with increasing SRTASP,T. When considering MS, however, the increase was significantly lower and leveled out over the investigated range of SRTASP,T, mainly due to corresponding WAS/MS ratios. This study demonstrates that the knowledge of SRTASP,T, sludge production, and anaerobic degradability enables the assessment of the potential of thermal hydrolysis and its effect on anaerobic digestion.